Effect of planting methods and drip irrigation intervals on onion (Allium cepa L.) yield under silt-loamy soil, Kassala State, Sudan - Khalifa, Ahmed; Algali2, Mohamed A.; Adlan, Adlan M. A.; Hamed, Ibtihal H. M.; Ali, Ali M.; Babiker, Ebtehag H.; Ahmed, Shaker B.; Yousif, Lotfie A.; Ali Babiker, Imad-eldin A.; Saeed, Amir B.; Ali, Mohamed A.; Heng, Lee (Gezira Journal of Agricultural Science; Vol 17 No 1 (2019), 2019)
The objective of this research work was to investigate the effects of planting methods and drip irrigation intervals on onion yield under silt-loamy soil. An experiment was conducted for two consecutive seasons (2014/15 and 2015/16). The experiment was composed of planting methods and drip irrigation intervals. The planting methods were flat, ridge and bed planting, whereas drip irrigation intervals were daily, every 3 days and every 5 days. The nine treatments were randomly laid out in a split-plot design with three replicates, the main plots were irrigation intervals and the subplots were allotted to planting methods. The calculated total water requirement for onion crop was 8113 and 7633 m 3 /ha in the first and second seasons, respectively. The results showed that the combination of flat planting and daily irrigation produced significantly the highest bulb weight (218.4g), marketable yield (43.8ton/ha) and highest total yield (46.6 ton/ha). The results revealed that flat planting and daily irrigation was the most economical combination for producing onion crop in Kassala state.            الهدف الرئيسي من هذه الدراسة هو دراسة تأثير طرق الزراعة وفترات الري بالتنقيط على نمو وانتاجية البصل تحت التربة الطميية في كسلا لموسمين متتاليين  ( 2014/15و(16/2015. تتكون التجربة من عاملين هما طريقة الزراعة وفترات الري بالتنقيط. طرق الزراعة هي احواض مسطحة، سراب وزراعة في مساطب، في حين كانت فترات الري بالتنقيط يوميا و3 أيام و 5 أيام. التسع معاملات وزعت عشوائيا في تصميم القطع المنشقة بثلاث مكررات، حيث وضعت فترات الري في الأحواض الرئيسية وطرق الزراعة في الأحواض الفرعية.  أظهرت النتائج أن طريقة الزراعة في احواض مسطحة مع الري اليومي اعطت أعلى وزن للبصلة مقارنة مع الزراعة في سراب ومساطب. تم الحصول على أعلى انتاجية تسويقية باستخدام الزراعة في احواض مسطحة والري اليومي. اثبتت النتائج ان الزراعة في احواض مسطحة والري بالتنقيط اليومي هي المعاملة الاقتصادية الاجدي لإنتاج محصول البصل في التربة الطميية في كسلا. وفقا للنتائج فإن أفضل طريقة لإنتاج البصل في كسلا هي باستخدام  الزراعة في احواض مسطحة والري اليومي.